Decomposition of Cyanide from Gold Leaching Tailingsby Using Sodium Metabisulphite and Hydrogen Peroxide. (7th October 2020) - Hou, Dongzhuang; Liu, Lang; Yang, Qixing; Zhang, Bo; Qiu, Huafu; Ruan, Shishan; Chen, Yue; Li, Hefu
Abstract : Cyanidation is widely used by most gold mine worldwide and will remain prevail in years (or decades) to come, while cyanide is hazardous, toxic pollutants whose presence in wastewater and tailings can seriously affect human and its environment; hence, it is necessary to control these contaminants. The purpose of this study was to examine the effects through the investigation of changes in pH, concentration, and contact time, and the optimal conditions were obtained. It has been proven that the decomposition of cyanide in solution and tailings increased as the alkalinity in the presence of 0.5 g/L Na2 S2 O5 . An increase in H2 O2 (30%) concentration (from 1 to 4 mL/L) increased the decomposition in solution, while the effect on removing cyanide was better when pH was 9 than 8 and 10 in tailings. The cyanide in tailings decreased in the first 4 h and increased after 4 h. The effective and economic conditions for maximum decomposition of cyanide from leach tailings are first treated in 0.5 g/L Na2 S2 O5 at pH 10 for 3 hours and then 2 mL/L H2 O2 (30%) is added to the tailings at pH 9 for 4 hours through comparative study. The findings provide the basis to optimize the decomposition of cyanide from gold leaching tailings in mining or backfilling by using the synergetic effect of Na2 S2 O5 and H2 O2 .